2020
DOI: 10.21203/rs.3.rs-27460/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Pharmacokinetic herb-drug interactions between Aidi injection and Doxorubicin in rats with diethylnitrosamine-induced hepatocellular carcinoma

Abstract: Background: Aidi Injection (ADI), a Chinese herbal preparation with anti-cancer activity, is used for the treatment of hepatocellular carcinoma (HCC). Several clinical studies have shown that co-administration of ADI with doxorubicin (DOX) is associated with reduced toxicity of chemotherapy, enhanced clinical efficacy and improved quality of life for patients. However, limited information is available about the herb-drug interactions between ADI and DOX. The study aimed to investigate the pharmacokinetic mecha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Therefore, we speculated that the combination of ADI and DOX may exert a synergistic antitumor effect. Our previous pharmacokinetic study confirmed that ADI can increase the concentration of DOX in plasma and tumors to treat HCC, and the associated mechanisms were related to DOX‐related drug metabolism enzymes and transporters (Lu et al, 2021). However, no relevant research has reported a synergistic antitumor mechanism for ADI combined with DOX from the perspective of endogenous metabolites.…”
Section: Introductionmentioning
confidence: 62%
“…Therefore, we speculated that the combination of ADI and DOX may exert a synergistic antitumor effect. Our previous pharmacokinetic study confirmed that ADI can increase the concentration of DOX in plasma and tumors to treat HCC, and the associated mechanisms were related to DOX‐related drug metabolism enzymes and transporters (Lu et al, 2021). However, no relevant research has reported a synergistic antitumor mechanism for ADI combined with DOX from the perspective of endogenous metabolites.…”
Section: Introductionmentioning
confidence: 62%